Neuronal primary cilia integrate peripheral signals with metabolic drives - DeMars, Kelly M.; Ross, Madeleine R.; Starr, Alana; McIntyre, Jeremy C. (Frontiers in Physiology, 2023)
Neuronal primary cilia have recently emerged as important contributors to the central regulation of energy homeostasis. As non-motile, microtubule-based organelles, primary cilia serve as signaling antennae for metabolic status. The impairment of ciliary structure or function can produce ciliopathies for which obesity is a hallmark phenotype and global ablation of cilia induces non-syndromic adiposity in mouse models. This organelle is not only a hub for metabolic signaling, but also for catecholamine neuromodulation that shapes neuronal circuitry in response to sensory input. The objective of this review is to highlight current research investigating the mechanisms of primary cilium-regulated metabolic drives for maintaining energy homeostasis.